Structures and systems vis-a-vis work ethic: priorities in administrative reforms - Rao, G.R.S. (1998)
Corruption at the higher levels, or in a few units of administration can be checked through institutions such as Lok Pal, Lok Ayukta or a Vigilance Commissioner. But, when it percolates from top to bottom, there is no chance of correction - it has to collapse. The plight of the third tier - the PRIs - resembles that of the monkey and two kittens, excepting that in this case it is more appropriate to liken the PRIs as the kitten, and the State and Centre as the two monkeys where there is no chance for the kitten to survive, let alone getting a crumb of bread. If a citizen violates a rule or a provision of law, he gets charged as a culprit and a criminal. But if an administrator violates a provision of law it merely gives rise to either a `complaint' or a `grievance' on the part of citizen. - Reproduced
Keywords: Administrative reform